CUSTOMER RELATIONSHIP MANAGEMENT DALAM MENINGKATKAN PENJUALAN PRODUK DI PT. HOLCIM INDONESIA, TBK. - Caroline, Julia; Suratmo, L.Y. Joko (MAJALAH ILMIAH WIDYA, 2012)
Customer Relationship Management is a strategy designed to create, maintain and to develop good realtions with potencialcustomers so as to change them become Customer Loyalty. This research is designed to acquire knowledge about the CustomerRelationship Management Strategic of PT Holcim Indonesia Tbk in maintaining good relationship with its distributors. This researchapplied a qualitative approach using case study model. The key informen are the Regional Sales Managers of PT Holcim IndonesiaTbk., and its distributors in Jakarta. The research shows that the incentive treatment given to the distributors is important and effetivelyto maintain the good relationship between the PT Holcim with itâs distributors.